Potential application of Pseudomonas stutzeri W228 for removal of copper and lead from marine environments. - Carolina Coelho da Costa Waite; Guilherme Oliveira Andrade da Silva; José Augusto Pires Bitencourt; Luciana Pereira Torres Chequer; Simone Pennafirme; Diogo de Azevedo Jurelevicius; Lucy Seldin; Mirian Araújo Carlos Crapez (PLoS ONE, 2020)
High concentrations of metals in the environment alter bacterial diversity, selecting resistant and tolerant species. The study evaluated the selection of a potential bacterial strain from Sepetiba Bay-Rio de Janeiro, Brazil marine sediments to remove Cu and Pb. The bacterial strain isolated from the sediments was used in three different bioassays: (1) Cu at concentrations of 0 (control), 6 and 50 μg.mL-1; (2) Pb at concentrations of 0 (control), 6 and 50 μg.mL-1; (3) Cu + Pb in concentrations of 3 μg.mL-1 Cu + 3 μg.mL-1 Pb (6 μg.mL-1) and 25 μg.mL-1 Cu + 25 μg.mL-1 Pb (50 μg.mL-1). The number of cells and the enzymatic activities of dehydrogenases and esterases were quantified. Results of taxonomic identification indicated the selection of the Pseudomonas stutzeri W228 strain, showing a greater degree of similarity (±73%) with the database used. There was no significant variation in the number of cells, 108 cells.mL-1, which represents a high biomass production in the presence of stressors. However, we observed a reduction in dehydrogenase activity at all tested concentrations of Cu, Pb and Cu + Pb. The activity of esterase increased, indicating a higher energy demand to complete the bacterial life cycle. The study showed significant results for the absorption of Pb by the extracellular polymeric substances (EPS) and the efflux of Cu. The capacity of Pb absorption by EPS can be considered a resistance mechanism, as well as the efflux of Cu, so that the available EPS sites could be occupied by the most toxic ions demonstrating that Pseudomonas stutzeri is resistant to Pb and Cu.